PERANCANGAN SISTEM INFORMASI UNTUK PENGELOLAAN KINERJA PEGAWAI DAN JEMAAT DI GEREJA MASEHI ADVENT HARI KE-TUJUH UNI INDONESIA BAGIAN BARAT - Henry Pandia (TeIKa, 2018)
Measuring employee productivity is a difficult task but a must if an organization want to managae and improve its employee performance. Therefore, and information system is needed which support organization in employee’s data recording process effectively. West Indonesian Union Mission (WIUM) is an organization that have hundreds employee that distributed in eight conferences/fields mission regionally separated, needs an information technology based system to acquire data and record all church’s and church pastor’s activities and services. The system will assist top management by giving adequate information in process of policy and decision making as well as careers promotion. Research aimed to develop a system that match WIUM’s requirements using System Development Life Cycle (SDLC) method, most popular method in information system development. Model that used in system development is waterfall model with stage: (1) Requirement Analysis, (2) Design (3) Implementation (4) Testing and (5) Maintenance. Result of Research is a web based information system that WIUM can use to record, store and share data and information of church’s and church pastor’s activities, services and performance.